Analysis of Productive Qualities of Pigs When Including DKB Feed Supplement in the Diet - Chernyshkov , Alexander; Zasemchuk, Inna; Semenchenko, Sergey (KnE Life Sciences, 2021)
Improving the efficiency of pig farming requires biologically complete feeding in accordance with the age, physiological and sexual characteristics of animals based on the knowledge of composition and nutritional value. The health and productivity of animals depends on the use of protein, fat, carbohydrates and minerals, and high-quality vitamins. Traditional feed does not provide animals with a sufficient and optimal ratio of minerals and vitamins. One of the factors providing young pigs with these nutrients may be the inclusion of the DKB vitamin-mineral energy supplement in the diet. The article analyzes the influence of DKB on the productivity of young pigs. The aim of the study was to justify an increase in productivity indicators of large white pigs feeding with DKB. In order to trace the impact of DKB on the productivity of pigs, we took into account the change in their live weight. During the experiment (60 days), 54 kg of the vitamin-mineral complex worth 3300 rubles was spent on the 20 piglets of the experimental group. This entailed an increase in the total costs. The results of the study indicate a positive effect of the additive on the dynamics and growth rate of the piglets of the experimental group and on the cost of feed and nutrients, which favorably affects the profitability and economic efficiency of pork production. Keywords: DKB vitamin-mineral energy supplement, piglets, live weight, growth dynamics, average daily gain, feed costs, profitability, economic efficiency